2003
DOI: 10.4315/0362-028x-66.5.866
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Aflatoxins by Korean Soybean Paste and Its Effect on Cytotoxicity and Reproductive Toxicity—Part 3. Inhibitory Effects of Korean Soybean Paste (Doen-jang) on Aflatoxin Toxicity in Laying Hens and Aflatoxin Accumulation in Their Eggs

Abstract: This study was conducted to determine the effects of Korean soybean paste (doen-jang [dwen-jahng]) (at concentrations of 0.5, 1, and 5%) on the toxicity of 500 ppb of aflatoxin in the diets of 60 laying hens (Isa Brown) divided into five groups and treated from week 15 to week 67. The aflatoxin-treated hens exhibited many deleterious effects, including reduced body weight; increased relative organ weights; decreased egg production; aflatoxin accumulation in eggs; decreased serum calcium, phosphorus, and alanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The ovaries showed follicular atresia which has a detrimental effect on egg production (Hafez et al, 1982;Pandey and Chauhan, 2007). Kim et al (2003) found a significant decrease in egg production and egg weights of laying hens fed on AFB 1 -treated ration. Washburn et al (1985) observed that AFB 1 resulted in reduction in egg size and increase in eggshell percentage, which was explained by the fact that aflatoxins are metabolized in the liver, where the synthesis and transport of the precursors required to yolk production occur.…”
Section: Fecunditymentioning
confidence: 99%
See 1 more Smart Citation
“…The ovaries showed follicular atresia which has a detrimental effect on egg production (Hafez et al, 1982;Pandey and Chauhan, 2007). Kim et al (2003) found a significant decrease in egg production and egg weights of laying hens fed on AFB 1 -treated ration. Washburn et al (1985) observed that AFB 1 resulted in reduction in egg size and increase in eggshell percentage, which was explained by the fact that aflatoxins are metabolized in the liver, where the synthesis and transport of the precursors required to yolk production occur.…”
Section: Fecunditymentioning
confidence: 99%
“…It is therefore very important to understand whether AFB 1 has various effects on the different stages of fish development, and whether the fish are able to tolerate AFB 1 during extended exposure to AFB 1 . In addition, previous studies have reported that AFB 1 contamination resulted in reduced egg production and quality in poultry (Kim et al, 2003;Oliveira et al, 2002;Pandey and Chauhan, 2007;Rizzi et al, 2003;Zaghini et al, 2005). Such studies are very limited in aquatic animals.…”
mentioning
confidence: 99%
“…This may be likely because of the physiological mechanism through which the effects of aflatoxin have been shown to operate in other species. For example in poultry, AFB 1 significantly decreased egg production, egg volume and serum oestradiol-17β concentrations [44][45][46]. In another study of Washburn et al [47] found out that AFB 1 caused a reduction in egg size and increase in eggshell percentage, which was attributed by the fact that aflatoxins are metabolized in the liver, where the synthesis and transport of the precursors required to yolk production occur.…”
Section: Effect Of Afb 1 On Reproductive Hormones Egg and Milt Qualimentioning
confidence: 99%
“…Aflatoxin has been recognized as a substance that retains to high temperature. Researchers are struggling to overcome the negative effects of aflatoxin B 1 by added promising natural substances or microorganisms such as soybean paste, lactic acid, and antagonist fungi of A. flavus (Bata and Latsztity 1999;Henry et al 1999;Kim et al 2003).…”
Section: Introductionmentioning
confidence: 99%